2002
DOI: 10.1046/j.1365-2133.2002.04961.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous marginal zone B-cell lymphoma: a clinical, histopathological, immunophenotypic and molecular genetic study of 22 cases

Abstract: MZCL appears to be a well recognizable entity, clinically, histologically and immunophenotypically. Although prognosis is generally good, the disease has potential for skin as well as extracutaneous recurrences. Large cell transformation and head and neck presentation may be associated with a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(65 citation statements)
references
References 22 publications
(52 reference statements)
1
63
0
1
Order By: Relevance
“…[8][9][10][11] However, in recent studies, extracutaneous dissemination and even death due to lymphoma have been reported more often. 12,13 Apart from case reports and small series of patients, studies specifically addressing the optimal treatment of PCMZL have not been published. Radiotherapy and surgical excision have been suggested as preferred treatments in patients with solitary or localized skin lesions, but published data on the treatment of patients with multifocal skin lesions are rare.…”
Section: Rimary Cutaneous Mar-mentioning
confidence: 99%
“…[8][9][10][11] However, in recent studies, extracutaneous dissemination and even death due to lymphoma have been reported more often. 12,13 Apart from case reports and small series of patients, studies specifically addressing the optimal treatment of PCMZL have not been published. Radiotherapy and surgical excision have been suggested as preferred treatments in patients with solitary or localized skin lesions, but published data on the treatment of patients with multifocal skin lesions are rare.…”
Section: Rimary Cutaneous Mar-mentioning
confidence: 99%
“…Most experts consider monoclonal a ratio of 5:1 or 10:1. Monotypic plasma cells can be found in 85% of the cases 84 : in two-thirds of cases, kappa is predominant, 84 and a heavy chain rearrangement is detected in about 60% to 70% of the cases. 84 Genetics t(14;18) (q32;q21) IGH/BCL2 and t(14;18) (q32;q21) IGH/MALT-1 were seen in cases of PCMZL with transformation toward higher-grade B-cell lymphoma.…”
Section: Histologymentioning
confidence: 97%
“…Primary cutaneous marginal zone B-cell lymphoma (PCMZL): Primary cutaneous marginal zone B-cell lymphoma may be manifested as single or multiple skin lesions and mainly develops in trunk and upper extremities [17]. In this study, two patients had single lesions.…”
Section: Image Characteristics Of Non-mf/ss CMLmentioning
confidence: 98%